Zoltán Dörnyei’s The Psychology of the Fruit of the Spirit with Implications Regarding Formational Theory and Practice - Issler, Klaus D. (Journal of spiritual formation & soul care, 2025)
In this academic-level and interdisciplinary study, Dörnyei claims that the fruit of the Spirit has an intended role as an important theological concept in Paul’s theology as encompassing Christlikeness, the goal of the Christian spiritual formation journey. Specifically, Dörnyei proposes that the nine-set fruit is of a unified and comprehensive nature and that this particular collective unit portrays the ideal Christian character. The essay describes key highlights of the study, evaluates these distinctive proposals, and recommends minor modifications. Finally, some implications are presented as next steps if we wish to let Paul’s concept of the fruit of the Spirit bear fruit both within our theoretical formational understanding and our practice as related to the catechism and systematic theology.